Pengaruh Trietanolamin pada Basis Krim Minyak dalam Air yang Berbahan Dasar Asam Stearat dan Setil Alkohol: Effect of Triethanolamine on Oil-in-Water Cream Base Based on Stearic Acid and Cetyl Alcohol - Novita Sari; Erwin Samsul; Angga Cipta Narsa (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
The cream is a semi-solid preparation with one or more ingredients dispersed in two types of emulsions, water-in-oil (W/O) and oil-in-water (O/W) type creams. Oil-in-water type cream has a high water content so that it can provide a hydration effect that can increase the penetration of the active substance. Triethanolamine in topical preparations is used as an emulsifier and alkalizing agent to form a homogeneous and stable cream. The purpose of this research was to determine the effect of triethanolamine on an oil-in-water cream base based on stearic acid and cetyl alcohol. Making the base is done by making preparations using four concentrations of triethanolamine 0.5% (F1), 1% (F2), 1.5% (F3), and 2% (F4). The cream base was then evaluated for its physical properties including organoleptic, homogeneity, pH, viscosity, spreadability, adhesion, and phase separation test. The results showed that in the organoleptic test cream bases were white, had a characteristic aroma with a semisolid form. The cream base has a homogeneity dispersion with an average pH between 6.53-7.29, viscosity between 3.5792396-3.8001904 (Pa.s), spreadability between 5.43-5.78 cm, and adhesion between 4.47-6.25 seconds. The cream base did not have phase separation and was stable in storage for 4 weeks at room temperature.